Random Mutagenesis of Lipomyces maratuensis InaCC Y720 Using Commercial UV Lamp To Increase Lipid Production - Agis Dwi Lestari; Atit Kanti; Miftahul Ilmi (Al-Kauniyah: Jurnal Biologi, 2024)
AbstractOleaginous yeasts are capable of accumulating high lipid concentration up to 20% of dry cell weight. High lipid content, a shorter life cycle, and similar a fatty acid composition to vegetable oils makes oleaginous yeast a potential lipid producer. Lipomyces maratuensis InaCC Y720 is a novel species isolated from Maratua Island, East Kalimantan, which has been reported as a potential yeast lipid producer. However, lipid productivity of the yeast is needed to be increased to make it suitable for an industrial scale. The aim of this study is to obtain potential mutant strains for the biodiesel industry. Random mutagenesis was applied by using commercial UV-C lamp on the strain which resulting in an 80% death rate after three hours irradiation. Subsequent treatment was carried out using cerulenin as a selection agent for mutans, yielding six mutant strains. Among these strains, mutant 1 produced the highest lipid production, with a lipid concentration of 0.072 g/L and a lipid percentage of 8.603%.  Nevertheless, when compared to the wild type, the lipid productivity of mutant 1 is low. Based on these results, the mutagenesis approach using commercial lamp UV-C has not obtained the expected mutants, so it is recommended to use different methods for future study.AbstrakKhamir oleaginous memiliki kemampuan dapat mengakumulasi lipid hingga 20% dari berat kering selnya. Tingginya kadar lipid yang diproduksi, siklus hidup yang pendek serta komposisi lipid yang mirip dengan minyak tumbuhan dapat menjadikan khamir sebagai alternatif penghasil lipid. Lipomyces maratuensis InaCC Y720 merupakan spesies baru yang diisolasi dari Pulau Maratua, Kalimantan Timur yang dilaporkan sebagai khamir penghasil lipid potensial. Namun, produktivitas lipid khamir tersebut perlu ditingkatkan agar sesuai untuk skala industri. Tujuan dalam studi ini adalah mendapatkan strain mutan yang potensial untuk industri biodiesel. Metode mutagenesis secara acak dilakukan dengan menggunakan lampu UV-C komersial pada strain yang menghasilkan tingkat kematian 80% selama tiga jam penyinaran. Setelah itu, dilakukan perlakuan lebih lanjut dengan penggunaan serulenin sebagai agen seleksi mutan. Proses seleksi menghasilkan enam strain mutan. Di antara keenam strain mutan, mutan 1 menghasilkan jumlah lipid tertinggi dengan berat lipid 0,072 g/L dengan persentase lipid yaitu 8,603%. Namun, dibandingkan dengan wild type, produktivitas lipid mutan 1 lebih rendah. Berdasarkan hasil ini, mutagenesis menggunakan lampu UV-C komersial belum mendapatkan mutan yang diharapkan sehingga disarankan penggunaan metode yang berbeda untuk penelitian selanjutnya.